Development of effective community participation framework in Gombe State, Nigeria - Umar, Saidu Alhassan (2020)
Desertification, land degradation, and drought constitute an environmental challenge that threatens the habitat of some of the globe's poorest populations located in the Sahara and Sahel zones. This led to the Great Green Wall Initiative to carry out sustainable restoration and local development activities. In 2013, the Nigerian federal ministry of environment strategies called for the frontline state's contribution and participation regarding communities' formal engagement at a local level. Gombe state, which was known for its rich agricultural landscape, beautiful forest, and shelterbelts, has rapidly turned into a desert due to deforestation caused by bush burning, overgrazing, and similar destructive human activities. Local communities of Gombe state have expressed their desire to be more involved in formulating and implementing policies that directly affect their livelihood. Few studies have currently explored the role of local governments in community participation processes and how it should be contextualized within local policy structures and practices. Gombe State is in the process of formulating community participation practices through policy. This research aims to establish sustainable local community participation in land resource conservation and management, thus enhancing local livelihoods. Case study research was used, which is well suited for exploratory research, where 20 Key Informant Interviews were conducted, where 11 are expert officials from various bodies, institutions, disciplines, and 9 are Committee leaders in Gombe local government. In order to gain local perspectives (community leaders), to explore the existing community participation policies, methods, and practices, and to learn more about expert local experiences (success and failures). This research identified community participation principles, strategies, and policy structures. This research found two types of practice; Firstly, theoretical mechanics of change which includes a formalized policy (values, principles, framework) and deliberative attention within the policy to diversity and empowerment; and Secondly, facilitation processes and resources of implementation that put theory into practice (e.g., community partnerships and champions). These findings inform the work of the Gombe Great Green wall directly and have implications for a framework of successful community participation in the local context that articulates how to develop and deliver community participation.